Identifying the source of mean and volatility spillovers in Irish equities: a multivariate GARCH analysis - Gallagher, Liam A.; Twomey, Cian E. (Economic & Social Studies, 1998)
This paper, using a multivariate VAR-GARCH analysis, examines the role of the UK stock market in the price behaviour of the ten largest Irish stocks. We identify the source of mean and volatility spillovers in Irish stocks by investigating interrelationships among industry sector, the overall UK and Irish markets, and individual Irish stock price movements. Significant mean and volatility spillovers exist from the UK to the individual Irish stocks. The relative size and significance of these spillovers from the UK indicate asymmetries in their effects on Irish stocks. Recent evidence of return spillovers from the UK to Ireland is not supported for all individual Irish stocks.
Keywords: Equities; Stock prices; Ireland; Multivariate analysis